Pelatihan Pengurusan Jenazah Perempuan untuk Menciptakan Pengurus Jenazah Perempuan di Padukuhan Serpeng - Rahma, Sabrur; Almardhiyah, Alaina; Phinasthika, Sekar Lintang; Nafi’ah, Salwa Qotrun; Mumtazah, Odhe Harlina Yumna; A’yun, Azmi Qurrota; Hafizhah, Haura Yumna (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
The training on female corpse management in Serpeng Hamlet, Pacarejo Village, Semanu District, Gunungkidul, is one of the community service programs conducted by KKN students of STIQ ZAD. This activity was motivated by the lack of understanding among the community, especially women, regarding the proper Islamic procedures for handling a deceased person. The training aimed to provide knowledge about the Islamic rulings on corpse management, enhance skills in bathing and shrouding the deceased, and supply shrouds as training materials at Nurul Hidayah Mosque.The implementation method included lectures and hands-on demonstrations, divided into two stages: the process of bathing and shrouding the deceased. This activity involved KKN students and the head of the women's religious study group in Serpeng Hamlet. The event, attended by approximately 40 participants, received very positive responses from the community. With this training, it is hoped that female corpse management cadres will emerge in Serpeng Hamlet, ready to fulfill this communal obligation (fardhu kifayah) in the future.